2021
DOI: 10.1016/j.heliyon.2021.e07452
|View full text |Cite
|
Sign up to set email alerts
|

Alkaloidal extract from Zanthoxylum zanthoxyloides stimulates insulin secretion in normoglycemic and nicotinamide/streptozotocin-induced diabetic rats

Abstract: Introduction: Increase in the prevalence of type-2 diabetes in Sub-Sahara Africa has created the need for robust treatment and management programs. However, an effective diabetes management program requires a high annual budget that most countries in this region cannot afford. That said, various plants and plant products in this region have either been confirmed and/or ethnopharmacologically used for the management of type-2 diabetes. Aim: To investigate the antidiabetic and insulin secretory effects of an alk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…With the advent of potential therapeutic methodologies, significant attempts have increased the effectiveness of natural anticancer medications [ 4 6 ]. A number of pharmacological actions, such as anti-bacterial, anti-spasmodic, chemopreventive, anticancer, and analgesic agents, have been attributed to isolated natural alkaloids and their analogues [ 7 , 8 ]. Besides this, it has been shown that C. papaya seeds are abundant in alkaloids that have anti-carcinogenic effects [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…With the advent of potential therapeutic methodologies, significant attempts have increased the effectiveness of natural anticancer medications [ 4 6 ]. A number of pharmacological actions, such as anti-bacterial, anti-spasmodic, chemopreventive, anticancer, and analgesic agents, have been attributed to isolated natural alkaloids and their analogues [ 7 , 8 ]. Besides this, it has been shown that C. papaya seeds are abundant in alkaloids that have anti-carcinogenic effects [ 9 ].…”
Section: Introductionmentioning
confidence: 99%